2013
DOI: 10.1021/ja411467p
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Carbene Ambiphilicity Leading to the Discovery of Reversible Ammonia Activation

Abstract: An N,N'-diamidocarbene (DAC) was found to activate a broad range of primary as well as secondary aliphatic and aromatic amines. The relative rates measured for the insertion of the DAC into the primary amines were consistent with an electrophilic activation mechanism; in contrast, the DAC functioned as a nucleophile upon treatment with secondary aryl amines. Collectively, these results constituted the first ambiphilic process for an isolable carbene. By comparison, an analogous diaminocarbene was found to serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…Recently, Bertrand and co‐workers reported the successful activation of N−H bonds of ammonia by ambiphilic CAAC under mild conditions . In addition, highly electrophilic diamido carbene (DAC) can activate ammonia ,. It was found that the primary approach for splitting of NH 3 by DAC is the interaction of amino lone pair with the vacant 2p orbital at the carbenic carbon whereas in case of CAAC the key step involves interaction of carbenic lone pair with one of the σ* N−H orbital of NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Bertrand and co‐workers reported the successful activation of N−H bonds of ammonia by ambiphilic CAAC under mild conditions . In addition, highly electrophilic diamido carbene (DAC) can activate ammonia ,. It was found that the primary approach for splitting of NH 3 by DAC is the interaction of amino lone pair with the vacant 2p orbital at the carbenic carbon whereas in case of CAAC the key step involves interaction of carbenic lone pair with one of the σ* N−H orbital of NH 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This discrepancy is attributed to their differences in the singlet‐triplet energy gap (46 kcal mol −1 CAACs vs 68 kcal mol −1 NHCs). Oxidative addition reaction of NH 3 with the saturated NHC ( 26 ) ( N,N ′‐dimesityl‐4,5‐dihydroimidazol‐2‐ylidene) was found to be reversible (Scheme b) . This is an important step towards catalysis as dynamic N−H activation will allow for transfer and/or release of the activated/functionalised product in catalytic turnover (Scheme , steps 3 and 4).…”
Section: Activation Of Small Molecules With Group 14 Complexesmentioning
confidence: 99%
“…[2] With some combinations of Lewis acids and bases these reactions are reversible, allowing their use in metal-free catalytic hydrogenation and other useful reactions. [8,9] Herein we report on anovel option for the metal-free activation of elemental-hydrogen s-bonds, making use of the salt 1(PF 6 ) 2 of the guanidino-functionalized aromatic (GFA) compound 1,2,4,5-tetrakis(tetramethylguanidino)benzene (1,s ee Scheme 1). Especially,c arbenes [3] and carbene-analogue species such as monomeric Al I compounds, [4,5] silylenes, or germylenes [6,7] insert (thermally or with light)i nto av ariety of different EÀHb onds.…”
mentioning
confidence: 99%